De la nuit et de l’obscurité : une étude icono-épigraphique maya - Cédric Becquey (Ateliers d'Anthropologie)
Although direct references to night are relatively rare in Maya texts and images from the Classic period, the value sign AHK’AB’ “night” is nevertheless omnipresent in them. As a component of glyphs, figures of speech or iconographic elements, the frequent use of the concept “night” makes it possible to construct meaning through idea association. It is therefore only by identifying all of this sign’s apparition contexts and by elucidating the associations involved that we might get close to conceptually defining that “night”. In this article, we will see that this approach allows us to get a sense of the great complexity of this concept, which can only be understood by diving into Maya cosmovision and mythology. In fact, it is particularly in its relation with the underworld or the primordial night that this “night” acquires a central place in the power legitimisation strategies of Maya elites.